A Short‐lived Three‐Belt Structure for sub‐MeV Electrons in the Van Allen Belts: Time Scale and Energy Dependence. Issue 9 (27th August 2020) - Hao, Y. X.; Zong, Q.‐G.; Zhou, X.‐Z.; Zou, H.; Rankin, R.; Sun, Y. X.; Chen, X. R.; Liu, Y.; Fu, S. Y.; Baker, D. N.; Spence, H. E.; Blake, J. B.; et al.
Abstract: In this study we focus on the radiation belt dynamics driven by the geomagnetic storms during September 2017. Besides the long‐lasting three‐belt structures of ultrarelativistic electrons (>2 MeV, existing for tens of days), which has been studied intensively during the Van Allen Probe era, it is found that magnetospheric electrons of hundreds of keVs can also have three‐belt structures at similar L extent during storm time. Measurements of 500–800 keV electrons from MagEIS instrument onboard Van Allen Probes show double‐peaked ( L = 3.5 and 4.5, respectively) flux‐versus‐L‐shell profile in the outer belt, which lasted for 2–3 days. During the time interval of such transient three‐belt structure, the energy‐versus‐L spectrogram shows novel distributions differing from both "S‐shaped" and "V‐shaped" spectrograms reported previously. Such peculiar distribution also illustrates the energy‐dependent occurrence of the three‐belt profile. The gradual formation of "reversed energy spectrum" at L  ∼ 3.5 also indicates that hiss scattering inside the plasmapause contributed to the fast decay of sub‐MeV remnant belt. Key Points: We report the existence of three‐belt structure composed by <1 MeV electrons The sub‐MeV three‐belt structure did not persist as those ultrarelativistic ones due to the fast (∼2 days) decay of remnant belt Sub‐MeV three‐belt structure is a transition phenomenon that shows comparable "old" and "new" electrons populations